2018
DOI: 10.3389/frma.2018.00026
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Perceptions, and Barriers to Research and Publishing Among Research and Teaching Staff in a Nigerian Research Institute

Abstract: The economic development of any nation is centered on research. Unfortunately, research activities had suffered serious setbacks in tertiary research institutions in Nigeria. This study explores the attitudes, perceptions, and barriers to research and publishing among academic staff in the Nigerian Institute of Leather and Science Technology, (NILEST) Zaria, Nigeria. A structured self-administered questionnaire was distributed among 130 research and teaching staff at the various Directorates in NILEST. Data ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…Yes, to a large extent, many results and claims about researches conducted in Nigeria today are exaggerated, however, it will be unfair not to acknowledge the genuine efforts of some researchers concerning the information they publish. It is also important to note that a large chunk of researches in Nigerian Universities and other institutions of higher learning are conducted during postgraduate training, which to a large extent are personally financed by the postgraduate students themselves with occasional support from some tutors [ 13 , 14 ]. In these circumstances, there can be no room for error.…”
Section: Status Of Research In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Yes, to a large extent, many results and claims about researches conducted in Nigeria today are exaggerated, however, it will be unfair not to acknowledge the genuine efforts of some researchers concerning the information they publish. It is also important to note that a large chunk of researches in Nigerian Universities and other institutions of higher learning are conducted during postgraduate training, which to a large extent are personally financed by the postgraduate students themselves with occasional support from some tutors [ 13 , 14 ]. In these circumstances, there can be no room for error.…”
Section: Status Of Research In Nigeriamentioning
confidence: 99%
“…This has hampered the image of Nigerian researchers and research institutions among their peers as successful publication of research brings attention to scholars and their institutions [ 23 ]. Recent studies have reported lack of funding, lack of research equipment and facilities, and inadequate training as some of the barriers that affect the conduct and publications of research findings among young researchers [ 14 ].…”
Section: Misconceptionsmentioning
confidence: 99%
“…Some of these perceptions include the importance of research in career advancement and in improving academics. This perception has been mentioned by other researchers such as (Bartel & Hagel, 2014;Okoduwa et al, 2018). Research publications are definitely important for career advancement such as academic promotion and for obtaining research awards.…”
Section: Resultsmentioning
confidence: 90%
“…Determination of the sample in this study using a saturated sample technique, meaning that the population is a sample. Data were collected using a questionnaire adapted from (Okoduwa et al, 2018). The questionnaire consists of 24 items that are divided into three parts, items (1-5) ask about perceptions of research publications, items (6-16) about challenges faced by lecturers in research production, and items from (17-24) about suggestions for increase research production.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Such programmes in all disciplines contribute greatly to the development of a nation and institutions of higher learning. [29]…”
Section: Postgraduate Nursing Research In South Africamentioning
confidence: 99%